Team’s performance on FIFA U17 World Cup 2011 : study based on notational analysis - Manuel Clemente, Filipe (2012)
The main objective of the notational analysis of the game includes optimizing feedback to the performer and coach to improve performance (Liebermann, Katz, Hughes, Bartlett, McClements & Franks, 2002). The main objective of this work was to analyze the profile of the teams that competed on FIFA U-17 World Cup at 2011, most exactly, trying understanding the offensive profile of the most successful teams. In this way we applied the test of correlation to verify if the goals for average are related to number of matches (i.e., more successful teams). There is statistical evidence to assert that the pairs (wins and goals) are positively moderating related (p = 0.001). In fact it appears that there is a directly intimacy between pairs (since the linear correlation coefficient r (24) = 0.774), i.e., how much more goals for average, more wins happens. Through the analysis of dependent variables is possible to say that teams who wins more games, have a superior mean of goals per match but, in the case of goals against, the teams that achieve the higher level in competition have higher mean of the goals against. However are the teams that play more matches that show higher level of goals for average.